Patent Right Competition Law Interface - Ozturk, O.; Ozturk, P. (IEEE, 2006)
Patent rights give the owners the right to exclude others from making selling and importing the patented invention. With this facade, patent rights pose a hindrance in front of the right to compete of third parties. Yet, in all legal systems it is generally accepted that to provide the technological and social development new ideas are essential and those ideas can be enhanced by granting the owners an exclusive right thereon. The owner of the patent right may either decide to use her invention in her own productions or she may chose to let others use it. This is a strategic decision to be taken by the patent owner in relation to her sources, manufacturing capacity, ability to penetrate the distribution channels etc. This paper aims to present the implications of competition law on patent rights, licensing of patent rights, technology transfer agreements and related legal transactions such as settlement agreements.